Fractal Characteristics of Coal and Sandstone Failure under Different Unloading Confining Pressure Tests - Tianran Ma; Depeng Ma; Yongjie Yang (Advances in Materials Science and Engineering)
To analyze the fractal characteristics of coal rock failure under unloading conditions, triaxial unloading confining pressure tests were carried out on coal and sandstone rock samples under different unloading rates and initial confining pressures. We examined the distribution of the surface cracks and fragmentation of the coal and sandstone samples that failed under different triaxial unloading confining pressure tests. The results showed that the fractal dimension of the surface cracks in coal and sandstone decreased as the initial unloading confining pressure increased. Thus, shear failure is more obvious in coal or sandstone with high-stress conditions caused by unloading confining pressure than in coal or sandstone with low-stress conditions. However, the fractal dimension of the surface cracks increased with the unloading rates. Additionally, the fractal dimension of the fragmentation in the coal and sandstone samples had a negative correlation with the initial unloading confining pressure. When the initial confining pressure was relatively low, the samples underwent splitting and shear failure; when the initial confining pressure was higher, the failure mode was mostly shear failure and the fragmentation of the samples was less homogeneous. In contrast, the fractal dimension of the fragmentation in the coal and sandstone increased with higher unloading rates. The lithology had a significant effect on the fractal dimension of the surface cracks and on the fragmentation. Samples with more internal fissures had more surface cracks and the fragmentation was more homogeneous when the rock failed compared with samples with less fissures under the same experimental conditions.